Zusanli (ST36) Acupoint Injection with Neostigmine for Paralytic Postoperative Ileus following Radical Gastrectomy for Gastric Cancer: a Randomized Clinical Trial - You, Xiaolan (J Cancer, 2018)
Background: The Zusanli (ST36) acupoint has been associated with treatment of various gastrointestinal conditions. There have been no studies of acupuncture therapy for paralytic postoperative ileus (PPOI). Materials and methods: Patients with PPOI following gastrectomy for gastric cancer were randomized to receive ST36 acupoint injection with neostigmine, gluteal intramuscular injection with 1.0 mg neostigmine, ST36 acupuncture alone, or standard therapy. The main outcome was the effectiveness rate for recovery of peristalsis. Secondary outcomes were time to bowel sound recovery, time to first flatus, and time to first defecation. Tertiary outcomes were drug-related adverse events, including abdominal pain, diarrhea, nausea, vomiting, tearing, delirium, seizure, and anxiety. Results: ST36 acupoint injection with neostigmine and gluteal intramuscular injection of neostigmine gave a higher rate of peristalsis recovery, and the ST36 acupoint injection group showed significantly higher total effectiveness rate than that of the intramuscular injection group. These interventions gave significantly shorter times to bowel sound recovery, shorter times to first flatus and first defecation compared with ST36 acupuncture and standard post-operative therapy (P < 0.01). ST36 acupoint injection group gave shorter time to bowel sound recovery, shorter time to first flatus and first defecation than those of the intramuscular injection group (P < 0.01). Drug-related adverse events in the intramuscular injection group were more serious than in the ST36 acupoint injection group (P < 0.05). Conclusion: ST36 acupoint injection with neostigmine is safe and effective for treatment of PPOI.